To be a Christian is not to be silent in the face of injustice: the Metropolitan Community Church (ICM) and the construction of a human rights church - Soares, Evanway Sellberg [UNESP] (Assoc Brasileira Historia Religioes-abhr, 2019)
This article aims to demonstrate the history of the Church of the Metropolitan community and how it was built as an inclusive church. For this it was used of participant observation in ICM-SP, as well as documentary research on denomination's websites, both national and international. In the end, it came to the conclusion that, despite having thematic focus in the fight for LGBT rights, the Church has a broader view of inclusion, fighting for human rights and that there is a strong relationship between the stories of the leadership of ICM and its perspective of inclusion.
Keywords: Metropolitan Community Church; Inclusion; Human Rights